2007
DOI: 10.1099/mic.0.2007/009936-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid inhibitors as novel antimycobacterial agents targeting Rv0636, a putative dehydratase enzyme involved in Mycobacterium tuberculosis fatty acid synthase II

Abstract: Flavonoids comprise a large group of bioactive polyphenolic plant secondary metabolites. Several of these possess potent in vivo activity against Escherichia coli and Plasmodium falciparum, targeting enzymes involved in fatty acid biosynthesis, such as enoyl-ACP-reductase, b-ketoacyl-ACP reductase and b-hydroxyacyl-ACP dehydratase. Herein, we report that butein, isoliquirtigenin, 2,29,49-trihydroxychalcone and fisetin inhibit the growth of Mycobacterium bovis BCG. Furthermore, in vitro inhibition of the mycoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…Several researchers have utilized nonpathogenic, fast-growing Mycobacterium species in rapid and easy screens for antimycobacterial activity in plant extract and pure plant-derived compounds (Brown et al, 2007;Kuete et al, 2008). In one study realized by McGaw et al (2008) was concluded that M. smegmatis was better predictor of activity against pathogenic M. tuberculosis.…”
Section: Antimycobacterial Activity Of the Fractions And Compounds Frommentioning
confidence: 99%
“…Several researchers have utilized nonpathogenic, fast-growing Mycobacterium species in rapid and easy screens for antimycobacterial activity in plant extract and pure plant-derived compounds (Brown et al, 2007;Kuete et al, 2008). In one study realized by McGaw et al (2008) was concluded that M. smegmatis was better predictor of activity against pathogenic M. tuberculosis.…”
Section: Antimycobacterial Activity Of the Fractions And Compounds Frommentioning
confidence: 99%
“…Dorstenia barteri Bureau., Moraceae, a small herb from most regions of tropical South America, contains active phytochemicals against bacteria and fungi. The dichloromethane : methanol (1 : 1) extract of it contains isobachalcone (26), kanzanol C (27), 4-hydroxylonchocarpin (28), stipulin (29), and amentoflavone (30). When comparing compounds from 27 to 30, isobachalcone was more active against M. smegmatis and M. tuberculosis [19].…”
mentioning
confidence: 99%
“…Compound 40 also acts synergestic with triclosan, a common additive of household products known to target InhA of bacterium and plasmodium [25]. Fisetin (41), from Cotinus coggygria syn Rhus continus Scop., Anacardiaceae, is an inhibitor of an unknown mycobacterial dehydratase (Rv0636) at MIC 63 µg/mL and is involved in mycolic acid synthesis [26]. Tryptophan aspartate containing coat protein (TACO) in macrophages prevents phagosome-lysosome fusion.…”
mentioning
confidence: 99%
See 2 more Smart Citations